Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27582
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Investigations of an Axial Compressor With Casing Treatment: Part 2 — Simulation

Abstract: A casing treatment with axial and radial skewed slots ending in a plenum chamber has numerically been investigated at a highly subsonic axial compressor stage. The aim was to understand the physical phenomena of this treatment family that are responsible for the stabilization of the blade passage flow and the drop in efficiency mostly observed. Unsteady 3D Reynolds-averaged simulations were performed with the commercial CFD Code TASCflow 2.12. The closure problem was faced with a standard k-ε high Reynolds tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The SMI for all 19 the CTs except for SP-4 is nearly equivalent with one another, which is consistent with the experimental conclusion for specific blade rotation speeds in Osborn et al 16 and Takata and Tsukuda. 17 From the overall performance comparisons, the plenum chamber can improve the compressor overall performance at the design point as CTs is implemented.…”
Section: Resultssupporting
confidence: 91%
“…The SMI for all 19 the CTs except for SP-4 is nearly equivalent with one another, which is consistent with the experimental conclusion for specific blade rotation speeds in Osborn et al 16 and Takata and Tsukuda. 17 From the overall performance comparisons, the plenum chamber can improve the compressor overall performance at the design point as CTs is implemented.…”
Section: Resultssupporting
confidence: 91%
“…The mechanism introduced by these casing treatments consists of fluid from low momentum regions near the blade tip being driven upstream of the blade and into the main flow region through the slots. Similar forms of casing treatment were used by Yu et al [21] and Emmrich et al [22,23]. A common finding of their work was that, due to a redistribution of the flow throughout the duct, the location where stall occurred changed from near the casing to a location near the hub.…”
Section: Passivementioning
confidence: 86%
“…23 displays isosurfaces of ν created for both stud cases in similar fashion as that created for the baseline case inFigure 5.18a. It is observed that now the low momentum region near the casing, as encased by the isosurface, extends from the blade flow passage, through the stator vanes, and all the way to the outlet plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, more and more studies are performed by computational fluid dynamics (CFD). Some mechanisms of casing treatment have been proposed (Emmrich et al, 2007;Lu et al, 2009;Muller et al, 2008). After several decades of research, casing treatment has been used in various compressors.…”
Section: Introductionmentioning
confidence: 99%